Higher viral load and genetic diversity of HIV‐1 in seminal compartments than in blood of seven Chinese men who have sex with men and have early HIV‐1 infection. (June 2017) - Jiao, Yan‐Mei; Chen, Guang‐Lei; Zhu, Wei‐Jun; Huang, Hui‐huang; Fu, Jun‐liang; Chen, Wei‐wei; Shi, Ming; Zhang, Tong; Wu, Hao; Wang, Fu‐Sheng
ABSTRACT: To date, there have been no reports characterizing HIV‐1 in the semen of Chinese men who have sex with men (MSM) with early infection. In this study, genetic diversity and viral load of HIV‐1 in the seminal compartments and blood of Chinese MSM with early HIV‐1 infection were examined. Viral load and genetic diversity of HIV‐1 in paired samples of semen and blood were analyzed in seven MSM with early HIV‐1 infection. HIV‐1 RNA and DNA were quantitated by real‐time PCR assays. Through sequencing the C2‐V5 region of the HIV‐1 env gene, the HIV‐1 genotype and genetic diversity based on V3 loop amino acid sequences were determined by using Geno2pheno and PSSM programs co‐receptor usage. It was found that there was more HIV‐1 RNA in seminal plasma than in blood plasma and total, and more 2‐LTR circular and integrated HIV‐1 DNA in seminal cells than in peripheral blood mononuclear cells from all seven patients with early HIV‐infection. There was also greater HIV‐1 genetic diversity in seminal than in blood compartments. HIV‐1 in plasma displayed higher genetic diversity than in cells from the blood and semen. In addition, V3 loop central motifs, which present some key neutralizing antibody epitopes, varied between blood and semen. Thus, virological characteristics in semen may be more representative when evaluating risk of transmission in persons with early HIV infection.